Pengaruh Struktur Modal, Likuiditas, Perputaran Persediaan Terhadap Profitabilitas pada Perusahaan Sub Sektor Makanan dan Minuman Terdaftar di Bursa Efek Indonesia (BEI) - Anisa Nurul Hidayah; Sri Hermuningsih; Alfiatul Maulida (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of capital structure, likuidity, and inventory turnover profitability in the food and beverages industry sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses quantitative research with sampling using purposive sampling method, which is a method of selecting samples with certain predetermined criteria. So that in this study, 26 data were obtained from 12 companies that met the criteria. This study used the multiple regression analysis method with the help of the spss program version 20. The results of this study show that: 1), capital structure the profitability. 2), Likuidity has no effect on the profitability. 3), inventory turnover has no effect on the profitability. 4), capital structure, likuidity, and inventory turnover together affect the profitability.